S.J. Gould's conception of non-overlapping magisteria - Herda, Justyna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2007)
There are many different approaches to the problem of the relation between science and religion. It is often claimed that there exists a conflict between those two domains. However, S. J. Gould cannot see neither how the two enterprises can stay in any conflict nor how they can be reconciled or unified. He developed a concept of two Non-Overlapping Magisteria (NOMA). Gould claims that science and religion are characterized by completely different areas of investigation. The two magisteria ask different questions and provide different explanations. Science investigates the factual character of the natural world while religion explores the world of values, meanings and purposes of human life. One could say that this is a reasonable point of view, but at a closer glance it does not seem to be a satisfactory solution.